A Quasiexperimental Study of the Bystander Plus Program for Changing Rape Culture Beliefs - Cadaret, Michael C. (Journal of interpersonal violence, 2021)
Sexual violence is considered a public health crisis and is particularly a problem on college campuses. Efforts for rape prevention at the collegiate level have included decreasing rape myth acceptance and increasing prosocial bystander behaviors. Although bystander models vary in regard to format and target population (e.g., male, female, or combined programs), they hold the same goals and underlying principles: to teach individuals how to effectively, and safely, intervene before, during, and after potential rape scenarios. In line with this research, the current study examined the efficacy of a bystander plus program, that goes beyond single session bystander focused programs to include a stronger focus on culture change and consciousness-raising across two sessions. The program was offered to undergraduate students (n = 23), the intervention group, over two sequential weeks. The first session was based on a modified version of Bringing in the Bystander, called Empowering the Bystander (ETB). ETB is a 60-min interactive session in which presenters provide information and lead discussions and activities aimed to address rape myths, to increase sexual assault survivor empathy, to learn prosocial bystander behaviors, and to increase awareness of rape culture at large. We followed this with a consciousness-raising group called Define It! that asked participants to define and operationalize concepts such as sexual assault and rape culture in their own lives. Students in an introductory psychology course served as a control group (n = 58) and did not receive the intervention. Both students within the intervention and control groups completed demographics and the Rape Culture Inventory (RCI) at pre-, post-, and 1-month postintervention. Results revealed a decrease in personal and perceived college endorsement of rape culture beliefs among intervention versus control participants. We discuss the implications of these results with concern to bystander programming and future directions for bystander plus program development.